Sensory Processing in Aquatic Environments 2003
DOI: 10.1007/978-0-387-22628-6_12
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Mediated Strategies to Counter Predation

Abstract: Predator-prey interactions govern the evolution of many behavioral and morphological traits of aquatic animals. In aquatic environments, chemical cues reliably allow prey to assess and avoid predation risk. In this chapter, I review the classes of chemical cues involved in a predation event and ways in which these cues mediate predator-prey interactions. Predators release signature odors that prey use to detect risk of predation. Prey release several types of cues. Chemical deterrents are noxious substances th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 167 publications
(119 reference statements)
1
64
0
Order By: Relevance
“…A wide range of animals learn to recognize predators from others, either indirectly through chemical cues of wounded individuals (Wisenden and Millard 2001;Wisenden 2003) or directly by observing experienced individuals interacting with predators (Curio et al 1978;Griffin et al 2000;Lönnstedt et al 2012), and both mechanisms may involve learning from conspecifics or heterospecifics (Curio et al 1978;Wisenden 2003;Magrath et al 2015). Previous studies showed that learning to recognize predators provides short-term survival benefits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A wide range of animals learn to recognize predators from others, either indirectly through chemical cues of wounded individuals (Wisenden and Millard 2001;Wisenden 2003) or directly by observing experienced individuals interacting with predators (Curio et al 1978;Griffin et al 2000;Lönnstedt et al 2012), and both mechanisms may involve learning from conspecifics or heterospecifics (Curio et al 1978;Wisenden 2003;Magrath et al 2015). Previous studies showed that learning to recognize predators provides short-term survival benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Animals have evolved different mechanisms to display appropriate antipredator responses (Wisenden 2003;Griffin 2004;Caro 2005;Hollén and Radford 2009). Some species have innate predator recognition, where individuals exhibit appropriate antipredator behaviors already during the first predator encounter in life (Curio 1993;Li 2002;Storm and Lima 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early detection is the key to achieving such an advantage, which can translate into fitness benefits (Lima and Dill, 1990;. In aquatic ecosystems, where information between conspecifics and other species is mostly shared via chemical cues, olfaction is the dominant sensory system and all major groups of aquatic organisms, from protists to amphibians, display defensive behaviours upon detection of predator odour (kairomone) or alarm cues released by damaged and consumed prey (Laurila et al, 1997;Wisenden, 2003;Lass et al, 2005). These chemicals often invoke immediate behavioural responses (and, if prolonged in time, morphological and life-history trait modifications) functioning to reduce the chances of predation .…”
Section: Introductionmentioning
confidence: 99%